The Urgency of Strengthening Tolerance Attitudes Through Problem-Based Fiqh Learning - 'In, Huril; Aziz, Imam Nur (Institut Islam Mamba'ul 'Ulum Surakarta, 2026)
This conceptual article aims to construct a theoretical argument for the urgency of transforming Fiqh learning through the Problem-Based Learning (PBL) model to strengthen students’ tolerance (tasamuh). The method used narrative research (literature review) with a descriptive-analytical approach to primary literature on Fiqh, pedagogy, and socio-religious studies. The analysis results show that PBL acts as a catalyst in shifting the paradigm from merely the transfer of knowledge to the transfer of values. Through the presentation of real, dilemma-laden, and context-specific problems, PBL encourages students to understand the diversity of schools of thought (khilāfāt), analyze the objectives of Islamic law (maqāṣid shari‘ah), and consider public welfare (maslahah). The process of value internalization in PBL occurs through three main phases: cognitive disorientation, collective ijtihad, and reflection and moral commitment. The conclusion of this article emphasizes that implementing PBL in Fiqh learning is effective in shaping students’ characters to be moderate, inclusive, and adaptable in responding to the pluralistic reality of Indonesian society.